The evaluation of software on critical path method/PERT / Aminuddin Mohamad and Khairuddin Idris - Mohamad, Aminuddin; Idris, Khairuddin (1987)
There are many techniques used to solved problems in Project Management such as Critical Path Method (CPM), Project Evaluation and Review Techniques (PERT) and others. On the other hand, additional tool are used to solve the problems more easier by using computer software that had been design specially for this purpose. So in this project the students are to evaluate the advantages of using computer software than the manual methods that based on CPM/PERT analysis in the Project Management.